Preparation and study Impact and Hardness Strength for Gravel Nano Particles /Polyester Composites - Essa, Abbas Fadhil (University of Thi-Qar Journal of Science, 2019)
In view of the developments of industrial applications, this happened in recent years and the need to use composite materials in general and polymer composite especially in the various industrial applications developed. This work focuses on studying the addition effect of the prepared gravel nanoparticles (different types) with particles size of (121.74 nm) for type( Ι ) and (100.16 nm)for type( ΙI ) as a nano particles with different weight percentages (10, 20, 30, 40) % to the unsaturated polyester resin (UPE) as a matrix to prepare polyester nanocomposites . The molding method was used to prepare polyester and their nanocomposites sheets.The mechanical properties were studied including Impact strength and Hardness strength for the samples. The results showed that the samples of Gravel nanocomposite type ( Ι ) gained highest values of Impact strength (4.508 KJ/m2 ) at ratio percents (40%) and the samples of Gravel nanocomposite type (IΙ ) gained highest values of Impact strength (5.509 KJ/m2) at ratio percents (40%). Also the results show that the UPE / Gravel nanocomposite type (IΙ ) gained highest values of Impact strength (5.509 KJ/m2) at ratio percents (40%) compared with UPE / Gravel nanocomposite type ( Ι ) (4.508 KJ/m2 ). Also the results showed that the samples of Gravel nanocomposite type (Ι) gained highest values of shore D number (91.65 H.NO.) at weight percentage (40%) of Gravel nano particales. While the samples of Gravel nanocomposite type (IΙ) gained highest values of shore D number (90.00 H.NO.) at weight Percentages (10%, 20%).